Plan de negocios para la creación de una empresa dedicada al proceso y comercialización de tomate rojo, verde y negro deshidratado en el Ecuador - Miranda Portilla, Arai Yuzara (2017)
The business plan is composed of eight chapters whose main objective is to verify the feasibility of implementing a company dedicated to the production and commercialization of dehydrated tomatoes in three varieties: red, green and black tomatoes. This company is part of the food processing industry, which is one of the industries with the greatest dynamism in the national economy, and has strong growth prospects due to the availability of agricultural products in the country. The market research presented in Chapter 3 showed that consumers are prone to acquire new products, especially if they come from organic farming processes. This strong trend towards the consumption of healthy foods and with high nutritional content of the last years has increased the opportunities for the new enterprises, especially in dehydrated products. These opportunities presented in the business will be developed in chapter 4 and the generation of a marketing plan aimed at increasing product promotion and sales, to finally arrive at the organizational structure proposal and the financial evaluation that will show the income, costs and expenses that determine the viability of the business plan based on the net present value of $ 32,078, which allows to recover the initial investment and obtain a profitability of 31.45%.